IoT-Based Public Street Lighting Monitoring and Control System Using LoRa Communication - Andi Ahmad Dahlan; Reza Fahlevi; Ummul Khair; A. Abd Jabbar (Brilliance: Research of Artificial Intelligence, 2026)
Public Street Lighting (PSL) systems are important infrastructures that support road safety, reduce criminal activity, and improve public comfort during nighttime conditions. However, conventional PSL systems still experience several limitations, including inefficient energy consumption, delayed maintenance processes, and the absence of real-time monitoring capabilities. This study aims to design and implement an Internet of Things (IoT)-based public street lighting monitoring and control system using LoRa communication technology and the MQTT protocol. The proposed system integrates ESP32 microcontrollers, LoRa E220-900T30D communication modules, Raspberry Pi gateway devices, MQTT brokers, and Node-RED dashboards. The system is also equipped with Light Dependent Resistor (LDR), Passive Infrared Receiver (PIR), and current sensors to support automatic lighting control, motion detection, and abnormal condition monitoring. The research method includes hardware and software design, system integration, and communication performance testing through local networks and internet connections. Experimental results show that the system successfully performs real-time monitoring and remote lighting control. The average transmission delay for node 1 was approximately 15 seconds, while node 2 experienced delays ranging from 21.89 seconds to 36.02 seconds depending on communication conditions and processor workload. The proposed system successfully improves operational monitoring efficiency, supports adaptive lighting control, and reduces energy consumption through dimmer-based lighting adjustment. The developed system can be implemented as an alternative smart city solution for intelligent and efficient public street lighting management.